A missense mutation in solute carrier family 12, member 1 (SLC12A1) causes hydrallantois in Japanese Black cattle. (December 2016) - Sasaki, Shinji; Hasegawa, Kiyotoshi; Higashi, Tomoko; Suzuki, Yutaka; Sugano, Sumio; Yasuda, Yasuaki; Sugimoto, Yoshikazu
Abstract Background Hydrallantois is the excessive accumulation of fluid within the allantoic cavity in pregnant animals and is associated with fetal mortality. Although the incidence of hydrallantois is very low in artificial insemination breeding programs in cattle, recently 38 cows with the phenotypic appearance of hydrallantois were reported in a local subpopulation of Japanese Black cattle. Of these, 33 were traced back to the same sire; however, both their parents were reported healthy, suggesting that hydrallantois is a recessive inherited disorder. To identify autozygous chromosome segments shared by individuals with hydrallantois and the causative mutation in Japanese Black cattle, we performed autozygosity mapping using single-nucleotide polymorphism (SNP) array and exome sequencing. Results Shared haplotypes of the affected fetuses spanned 3.52 Mb on bovine chromosome 10. Exome sequencing identified a SNP (g.62382825G > A, p.Pro372Leu) in exon 10 of solute carrier family 12, member 1 (SLC12A1 ), the genotype of which was compatible with recessive inheritance. SLC12A1 serves as a reabsorption molecule of Na+ -K+ -2Cl− in the apical membrane of the thick ascending limb of the loop of Henle in the kidney. We observed that the concentration of Na+ -Cl− increased in allantoic fluid of homozygousSLC12A1 (g.62382825G > A) in a hydrallantois individual. In addition, SLC12A1-positive signals were localized at the apical membrane in the kidneys of unaffected fetuses, whereas they were absent from the apical membrane in the kidneys of affected fetuses. These results suggested that p.Pro372Leu affects the membrane localization of SLC12A1, and in turn, may impair its transporter activity. Surveillance of the risk-allele frequency revealed that the carriers were restricted to the local subpopulation of Japanese Black cattle. Moreover, we identified a founder individual that carried the mutation (g.62382825G > A). Conclusions In this study, we mapped the shared haplotypes of affected fetuses using autozygosity mapping and identified a de novo mutation in theSLC12A1 gene that was associated with hydrallantois in Japanese Black cattle. In kidneys of hydrallantois-affected fetuses, the mutation inSLC12A1 impaired the apical membrane localization of SLC12A1 and reabsorption of Na+ -K+ -2Cl− in the thick ascending limb of the loop of Henle, leading to a defect in the concentration of urine via the countercurrent mechanism. Consequently, the affected fetuses exhibited polyuria that accumulated in the allantoic cavity. Surveillance of the risk-allele frequency indicated that carriers were not widespread throughout the Japanese Black cattle population. Moreover, we identified the founder individual, and thus could effectively manage the disorder in the population.